Dynamic Response Solution of Multi-Layered Pavement Structure Under FWD Load Appling the Precise Integration Algorithm - Han, Zejun; Fang, Hongyuan; Zhang, Juan; Wang, Fuming (Computers, materials & continua, 2019)
The pavement layered structures are composed of surface layer, road base and multi-layered soil foundation. They can be undermined over time by repeated vehicle loads. In this study, a hybrid numerical method which can evaluate the displacement responses of pavement structures under dynamic falling weight deflectometer (FWD) loads. The proposed method consists of two parts: (a) the dynamic stiffness matrices of the points at the surface in the frequency domain which is based on the domain-transformation and dual vector form equation, and (b) interpolates the dynamic stiffness matrices by a continues rational function of frequency. The mixed variables formulation (MVF) can treat multiple degree of freedom systems with considering the coupling term between degree of freedoms. The accuracy of the developed method has been demonstrated by comparison between the proposed method and published results from the other method. Then the proposed method can be applied as a forward calculation technique to emulate the falling weight deflectometer test for multi-layered pavement structures.